Two new species of Proisotoma Börner, 1901 from Southeastern Brazil (Collembola: Isotomidae) - Cleide de Mendonça, Maria; Queiroz, Gabriel Costa; da Silveira, Tatiana Cristina (Soil Organisms, 2015)
Two new species of Proisotoma from different Biological Conservation Unities of southeastern Brazil are described: P. douglasi sp. nov., found in Parque Nacional de Itatiaia (Rio de Janeiro State) and P. copiosa sp. nov., from Sooretama Biological Reserve (Espírito Santo State). We observed a presence of spine chaetae on antennae of males and 2 chaetae inserted on papillae laterally on tibiotarsus III in males and females in P. copiosa sp. nov.
Keywords: Atlantic Forest; Biodiversity; Brazilian Páramos; Taxonomy